Evaluation of sensory and bromatological characteristics of a strawberry gum (Fragaria x ananassa Duch) with addition of yuca (Manihot esculenta Crantz) (Agroindustria, Sociedad y Ambiente, 2019)
At present there is a great variety of functional foods on the market. The use of natural ingredients in the elaboration of these products, with innovative materials incorporated in the mixtures favors the formulation of healthy products. The innovation possibilities mentioned above may be represented by a raw material with little research in the agro- industrial area, such as cassava, a traditional crop of great importance in Venezuela. The objective of the work was to elaborate a formulation of a candy, gummy type with different proportions of cassava flour and with the same proportion of strawberry. The study was carried out in three phases, in the first phase the formulation and elaboration of the strawberry jelly was made with the addition of 5%, 7% and 10% cassava flour. In the second phase, the sensory evaluation, degree of satisfaction and preference of the formulation were carried out with 80 untrained panelists composed of children from 9 to 14 years of age and in the third phase, the bromatological analysis of the strawberry jelly with addition of cassava flour that resulted in the greatest satisfaction of consumers (determination of total protein, total ashes, moisture and total carbohydrates, raw fiber, total fat and metabolizable energy). A completely randomized design was used, with three treatments, the analysis of variance (simple ANOVA) was performed using the STATGRAPHICS Centurion XVI program, the data obtained in the sensory assessment of satisfaction and preference for the attributes smell, texture and taste A non-parametric analysis was performed by applying the Kruskal-Wallis test. The results of the formulation of strawberry gummies, with proportions of 5, 7 and 10% of cassava flour addition, showed acceptable characteristics and without defects for consumers, in the sensory assessment the formulation with 5% addition of Cassava proved to be more pleasing in the degree of consumer satisfaction. The bromatological characteristics showed contents of Humidity of 11.57%, Proteins 3.50%, Fat 2.69%, Carbohydrates 92.81%, Ashes 0.177, Fiber 0.82% and energy intake 125 calories.
Keywords: Formulation; bromatological analysis; sensory evaluation